Complications after autologous fat grafted into residual capsular sac after removal of breast prosthesis: Case reports - Ting Li; Yi Sun; Sufan Wu; Ce Zhang (Heliyon)
Background: Fat grafting after breast prostheses removal has been performed widely for the breast augmentation. However, the postoperative complications and clinical safety of these two procedures are still widely concerned. Here, the authors presented two clinical cases of the complications of autologous fat grafting after breast prostheses removal.Methods: two patients visited our outpatient department, the one of them consulted for a 10-day history of fever and swelling of the left breast, the another consulted for the immovable mass in the left breast. Both of them received the surgery of bilateral breast prostheses removal there years ago and received the surgery of autologous fat grafting to the breasts in the year interval between surgeries. Based on the patient's history, physical examination and magnetic resonance imaging (MRI) examination, the fibro-oil cysts and fibrocystic mass formation were observed in patient A and patient B, respectively. Results: Incision and drainage were performed immediately with the patients. In one patient, a delineated capsular sac was revealed upon dissecting the pectoralis major during intraoperative exploration. Within this sac, a substantial quantity of grey-yellow fibro-oil cysts containing yellow. In another patient, upon dissecting the capsular sac, a fibrocystic mass containing necrotic adipose tissue was observed. Histopathological analysis of the fibro-oil cysts and the fibrocystic mass revealed that the surrounding envelope consisted of fibrous cystic parietal tissue enclosing pale and mildly lipid necrotic tissue. Conclusion: These results indicated that the main reason for the occurrence of these complications might be grafting fat into the remaining capsular sac. In a word, while performing the procedure of breast prosthesis removal, it is imperative to thoroughly excise the capsular sac to prevent the creation of residual capsular sac; Autologous fat should be inserted in multiple directions and correct layers. Prior to surgery, thorough preoperative positioning examinations should be conducted to avert the inadvertent injection of autologous fat.